Public Acceptance of New Criminal Law Policies in Cases of Violence - Azmi, Sefiani Dwi (Journal of Adat Recht, 2025)
This study aims to explore public acceptance of the new criminal law policy implemented in handling cases of violence in Indonesia. Using a qualitative approach, this study used in-depth interviews and focus group discussions to collect data from various levels of society, including victims of violence, perpetrators, law enforcers, and members of the general public. The results show that although there is positive acceptance of increased sanctions and legal reforms aimed at protecting victims, there are concerns about the implementation and consistency of law enforcement. Many respondents expressed the need for better education and social support to ensure that the policy is effective in practice. These findings provide important insights into how the new policy is received in the field and what obstacles are faced in the implementation process. This study is expected to be a reference for policy makers and legal practitioners in formulating more effective strategies in handling cases of violence in the future.